Decentralization and electoral accountability : incentives, separation, and voter welfare - Jean Hindriks; Benjamin Lockwood (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper studies the relationship between fiscal decentralization and electoral accountability, by analyzing how decentralization impacts upon incentive and selection effects, and thus on voter welfare. The model abstracts from features such as public good spillovers or economies of scale, so that absent elections, voters are indifferent about the fiscal regime. The effect of fiscal centralization on voter welfare works through two channels: (i) via its effect on the probability of pooling by the bad incumbent; (ii) conditional on the probability of pooling, the extent to which, with centralization, the incumbent can divert rents in some regions without this being detected by voters in other regions (selective rent diversion). Both these effects depend on the information structure: whether voters only observe fiscal policy in their own region, in all regions, or an intermediate case with a uniform tax across all regions. More voter information does not necessarily raise voter welfare, and under some conditions, voters would choose uniform over differentiated taxes ex ante to constrain selective rent diversion.
Keywords: H41; D73; D72; 330; Finanzföderalismus; Finanzpolitische Aufgabenverteilung; Politische Willensbildung; Good Governance